The Effectiveness of Moringa Leaves in Controlling Blood Sugar Levels in Patients With Type 2 Diabetes Mellitus in Prolanis, Sampang District, Madura - Anik Handayati; Pestariati Pestariati; Suhariyadi Suhariyadi (Frontiers in Community Service and Empowerment, 2022)
Diabetes mellitus (DM) is a disease that leads to an increase in blood glucose levels, which in turn can lead to chronic diseases. The potential group to be socialized is the Prolanis group at Sreseh Health Centre, Sampang Madura. Moringa is a tree that grows very commonly in the Madura region, including in Sreseh sub-district. Moringa contains active ingredients that can lower blood glucose levels. People do not avail of the benefits of Moringa leaves  (Moringa aleivera), which are widely available in the region. The purpose of this community service activity is so that the community can be more optimal in controlling blood sugar levels, especially the use of Moringa leaf extract in lowering blood sugar levels. The method of conducting the activities is a group-based method that is carried out comprehensively, namely conducting regular and continuous counselling and consultations for Prolanis members. The activities of the community service teams are carried out in a measurable way and a monitoring and evaluation process is carried out to measure the achievement of the objectives and results. The results of the PKM activities have been identified: Community service activities (PKM) that have been well implemented, starting with survey and coordination activities, initial assessment activities, PKM implementation activities, and evaluation of the results achieved. The community, in this case, the Prolanis members with DM type 2, participated with great enthusiasm in each meeting/phase of the activities. The evaluation of the results of the activities showed good results: The number of subjects with type 2 diabetes whose blood glucose levels were uncontrolled decreased by 61.54%.